Adsorption of P-Aminodiphenylamine with Iodine Charge Transfer Complex on Surface Arundo Plant - R. Mamdoh, Zainab; S. Abd-Ulrazzaq , Sahira (Al-Nahrain Journal of Science, 2019)
A charge transfer complex formed by interaction between the p- aminodiphenylamine (PADPA) as electron donor with iodine as electron acceptor in ethanol at 250C as evidenced by color change and absorption. The spectrum obtained from complex PADPA – Iodine shows absorptions bands at 586 nm. All the variables which affected on the stability of complex were studies such as temperature, pH, time and concentration of acceptor. The linearity of the method was observed within a concentration rang (10–165) mg.L-1 and with a correlation coefficient (0.9996), while the molar absorbitivity and sandell sensitivity were (4643.32) L.mol-1.cm-1 and (0.0943) µg.cm-2, respectively. The adsorption of complex PADPA–I2 was studied using adsorbent surfaces arundo plant. The dynamics of isotherm were studied according to experimental conditions of contact time, adsorbent weight, pH and particle size. The results showed the adsorption isotherm according to the Gils classification indicated L1, when the temperature (10,25)0C of plant, but S2 at (37.5,50) 0C for plant. Analytical techniques including UV-Vis. & FTIR were applied to characterize arundo. The values of Gibbs free energy, enthalpy ,entropy calculated from the thermodynamics of the process.